الاستخدامات المهنية لشبكة لينكدإن في التعليم العالي والبحث العلمي منظور تحليلي (مجلة الواحات للبحوث والدراسات, 2021)
Recently, The Use Of Social Networks Has Greatly Expanded Thanks To Its Large Number Of Services Targeting All Professionals Worldwide. This Research Attempts To Analyze The Most Important Ways To Use Social Networks By University Teachers And Researchers. By Focusing On The Linkedin Network, And Recalling Its Benefits, The Best Ways To Use It In Scientific Research As Well Communities Of Practice Related To Scientific Research And Higher Education, As Seen Through This Network.  Key Words: Social Networking, Linkedin, Professional Use, Scientific Research, Communities Of Practice